Poverty and the Poor in the Media Discourse in Poland: Compassion or Blame? - Pokrzywa, Magdalena (Katolicki Uniwersytet Lubelski Jana Pawła II, 2023)
The purpose of this article is to show how poverty and the people who experience it are presented by various media (press, television programmes, etc.) in Poland. Referring to research and media analyses of the representation of this phenomenon, attempts were made to reveal the causes and valuations attributed to it. The media discourse on poverty shapes and proliferates social perceptions about it. It is crucial because it influences how fellow citizens treat the poor and policies aimed at minimising this phenomenon. Two dominant mass media narratives about those affected by poverty can be divided as follows: 1) the deserving poor worthy of support because their poverty is due to external sources beyond their power, and 2) the undeserving poor, who are themselves responsible for their material situation due to bad attitudes, habits, and deviant behaviours. Celem artykułu jest ukazanie w jaki sposób przedstawiane jest ubóstwo i osoby go doświadczające przez różne środki masowego przekazu (prasa, programy telewizyjne, itp.) w Polsce. Odwołując się do badań i analiz medialnych reprezentacji tego zjawiska starano się wyeksponować przypisywane mu przyczyny i wartościowanie. Dyskurs medialny na temat ubóstwa zarówno kształtuje, jak i powiela społeczne wyobrażenia o nim. Jest istotny, gdyż wpływa na sposób traktowania biednych przez współobywateli oraz polityki mające na celu minimalizację tego zjawiska. Można wyodrębnić dwa dominujące typy narracji środków masowego przekazu na temat biednych, jako: 1) zasługujących na wsparcie ze względu na zewnętrze w stosunku do nich czynniki losowe będące źródłem ich ubóstwa oraz 2) niezasługujących, którzy są sami winni swojej sytuacji materialnej ze względu na złe postawy, nawyki i dewiacyjne zachowania.